Personality, Group Decision-Making and Leadership - Seda Ertac; Mehmet Y. Gurdal (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This paper explores the effect of personality traits on: (1) the willingness to make risk-taking decisions on behalf of a group, (2) the nature of "choice shifts", i.e. the difference between the amount of risk taken in the group context and individually. Openness and agreeableness emerge as significant determinants of the willingness to lead: non-leader women and non-leader men score lower on openness and higher in agreeableness compared to both leader men and leader women. Neuroticism explains the within-gender variance in individual risk-taking among women, who are on average more risk-averse than men. Subjects in general behave more cautiously when they are making risky decisions on behalf of a group. Among men, a higher agreeableness score implies higher caution in group decisions, while conscientiousness leads to less caution. In contrast, among women, a higher conscientiousness score implies higher caution in the group context, suggesting that the two genders might interpret the social norms in group decision-making differently.
Keywords: C91; C92; D81; J16; 330; personality; leadership; gender; group decision-making; risk; choice shifts; experiments; Führungspersönlichkeit; Geschlecht; Gruppenentscheidung; Entscheidung unter Risiko; Test